The psychological syndrome associated with Long-COVID: A study protocol - Gómez Bravo, Raquel; Infanti, Alexandre; Billieux, Joël; Ritzen, Mark; , Psy-Long-COVID Consortium; Vögele, Claus; Benoy, Charles; Mortiz, Steffen; Erhardt, Angelika; Staub, Thérèse; Huber, Christian; Lang, Undine; et al. (Frontiers in Epidemiology, 2023)
Chronic post-viral syndromes, including Long-COVID, are characterized by a range of persistent symptoms that occur following a viral infection. Psychological symptoms are prevalent in Long-COVID patients and can have a significant impact on their quality of life. However, the specific patterns of psychological symptoms, their associations with physical symptoms, and the factors predicting their severity remain poorly understood. Aims This study aims to explore and systematically assess psychological symptoms in Long-COVID, to identify syndrome clusters based on these symptoms, to examine their relationship with physical symptoms, and to investigate the influence of pandemic-related variables. Methods: Descriptive, cross-sectional study with data collected through an online questionnaire across several EU countries, from February 2020 to December 2022. Participants were recruited using public relations, the social media and information campaigns directed at the public and health professionals using snowball sampling. Results: The findings will allow for the first-time to phenotype Long-COVID related psychological symptom clusters based on self-reports. facilitating improved assessment and treatment approaches. Conclusions: The results will provide important knowledge for the public health management of the ongoing pandemic. The findings will contribute to a better understanding of the psychological symptoms associated with Long-COVID and the development of specific treatment guidelines for psychological burden associated with Long-COVID, thereby supporting management strategies to combat the after-effects of the COVID-19 pandemic, enhancing their overall well-being and quality of life.